2021
DOI: 10.3390/ijms22115534
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Inhibits the Transporter Function of the Blood-Brain Barrier by Directly Interacting with the ABC Transporter Breast Cancer Resistance Protein (BCRP)

Abstract: The breast cancer resistance protein (BCRP) is an important efflux transporter in the blood-brain barrier (BBB), protecting the brain from a wide range of substances. In this study, we investigated if BCRP function is affected by bisphenol A (BPA), a high production volume chemical used in common consumer products, as well as by bisphenol F (BPF) and bisphenol S (BPS), which are used to substitute BPA. We employed a transwell-based in vitro cell model of iPSC-derived brain microvascular endothelial cells, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Indeed, TBBPA inhibited the crucial gene expression related to the blood–brain barrier in zebrafish larva head tissue. The analogue BPA exposure could damage blood vessels and the blood–brain barrier and induce brain atherosclerosis, linked to neuroinflammation and nervous system disorders. Similarly, our previous studies also suggested that cerebrovasculature is a more sensitive target than neuronal effects for flame retardant exposure. , In line with the in vivo study, the in vitro study also demonstrated that TBBPA inhibited cell migration and angiogenic signaling pathways in primary neuroendothelial cells. These data indicate that the neurovascular impairment may be the susceptible target at the early neurodevelopmental stage as well as suggest that the potential contribution of our data to both aquatic toxicity assessment and human health risk assessment.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, TBBPA inhibited the crucial gene expression related to the blood–brain barrier in zebrafish larva head tissue. The analogue BPA exposure could damage blood vessels and the blood–brain barrier and induce brain atherosclerosis, linked to neuroinflammation and nervous system disorders. Similarly, our previous studies also suggested that cerebrovasculature is a more sensitive target than neuronal effects for flame retardant exposure. , In line with the in vivo study, the in vitro study also demonstrated that TBBPA inhibited cell migration and angiogenic signaling pathways in primary neuroendothelial cells. These data indicate that the neurovascular impairment may be the susceptible target at the early neurodevelopmental stage as well as suggest that the potential contribution of our data to both aquatic toxicity assessment and human health risk assessment.…”
Section: Discussionsupporting
confidence: 57%
“…These results suggest that the 3D-BBB system can evaluate the function of the BCRP as well as the 2D model, and may therefore prove useful in applications such as disease modeling and toxicity evaluation in the future. This is important, because BCRP is more highly expressed than P-gp in the human BBB (43), and functional changes of BCRP at the BBB are associated with various diseases (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…52 A similar ability to disrupt efflux transport in the BBB has also been observed for the flame retardant tetrabromobisphenol A, 53 the wood preservative 2,4,6-tribromophenol, 54 and the endocrine disruptor bisphenol A. 55 Disruption of transport at the BBB by environmental toxicants may weaken this key mechanism of neuroprotection.…”
Section: Blood-brain Barriermentioning
confidence: 61%